Handbook of families & poverty - Crane, D. Russell; Heaton, Tim B.; Sage eBooks (Los Angeles, [Calif.] ; London : SAGE, 2008)
Written by respected scholars from a variety of disciplines this book will cover hotly debated issues associated with public policy and funded research as they relate to families and poverty.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Poverty -- United States; Poor families -- United States; Families -- United States; Economic assistance, Domestic -- United States; Public welfare -- United States; Electronic books